A neutral‐metabolic theory of latitudinal biodiversity. Issue 6 (2nd April 2016) - Tittensor, Derek P.; Worm, Boris
Abstract: Aim: Latitudinal gradients of species richness represent Earth's first‐order biodiversity pattern. Most species groups display a near‐monotonic decline in richness from the equator to the poles, yet there exists little mechanistic theory to derive such patterns from first principles. Here we integrate two key advances – neutral theory and the metabolic theory of ecology – to reconstruct global species richness gradients and test underlying causes. Location: Simulated global meta‐community. Methods: We constructed a spatially explicit global meta‐community with constant per capita rates of disturbance, speciation and dispersal. No gradient emerged in this neutral base model. Focusing on the oceans as a model system, we added a water temperature gradient of 0–30°C that independently affected rates of community turnover and speciation based on established metabolic scaling laws. We also added a gradient in habitat area that roughly parallels the observed decrease in ocean area from tropical to polar waters. Results: Thermal effects on the community turnover rate caused a transient latitudinal gradient that ultimately disappeared. Thermal effects on speciation produced a dynamically stable but relatively weak gradient. Increasing habitat area towards the equator in combination with thermal effects on speciation rate produced a more realistic gradient that emerged from the combined effects of species–area and species–energy theory. Main conclusions: This reasonably simple model provides a platform to explore support for processes underpinning large‐scale biodiversity gradients, and the ability of prominent ecological theories, independently or in combination, to capture them.